Imaginary travellers : identity conceptualisations of the audience among travel journalists - Duffy, Andrew (2019)
Travel journalists cannot know each traveller for whom they write, so they must imagine what a reader wants. The subsequent journalism influences how tourists travel and engage with a foreign country and its inhabitants. This article uses an independent/connected framework of tourist behaviour to identify how travel journalists imagine their readers’ interests. Through content analysis of texts in newspapers from Asia and the West, we find that the reader is more often imagined as independent and adventurous than connected and concerned with tourist sights. However, the latter were more common in Asia, which suggests that travel writers across the globe imagine readers differently. It suggests that in an increasingly globalised world, the post-colonial power dynamic that has been a stalwart of scholarly thought on travel writing may be outdated and could be more usefully replaced by one that considers the financial privilege of tourism, seen in texts from both hemispheres.